Implementation of the TPKS Law In DIY From the Perspective of Policy Network Theory - Husein, Zahmil; Rangga, Rangga; Andika Putra, Kevin; Padillah, Muhammad; Djou, Muhammad Nabiel Azirah; Septiyanti, Gea Ananda Putri (Journal Governance Bureaucratic Review, 2025)
The increasing prevalence of sexual violence in Indonesia has posed a major governance challenge, prompting the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law). Despite this progressive legal framework, its implementation at the local level, particularly in the Special Region of Yogyakarta (DIY), remains fraught with structural, institutional, and socio‐cultural obstacles. This study aims to analyze how the TPKS Law is implemented within the context of multi‐actor collaboration by employing Policy Network Theory as an analytical lens. The research seeks to identify key actors, map their relationships, and evaluate how coordination mechanisms influence policy outcomes. Using a qualitative descriptive approach, the study draws upon secondary data sources, including government reports, academic publications, and NGO documentation, which were analyzed through content and thematic analysis. The findings reveal that the effectiveness of the TPKS Law depends largely on the strength of horizontal coordination among actors such as the Yogyakarta Regional Police, DP3AP2 DIY, NGOs like and local communities. While legal institutions provide authority and structure, NGOs contribute trust and community engagement, creating a complementary but asymmetrical network. The study concludes that successful implementation of the TPKS Law in Yogyakarta requires adaptive governance practices characterized by continuous learning, inter‐agency collaboration, and community participation.